ANALISIS KINERJA SOSIAL DAN KINERJA KEUANGAN LEMBAGA KEUANGAN MIKRO (LKM) USAHA EKONOMI DESA-SIMPAN PINJAM (UED-SP) SEJAHTERA DESA TELUK MERBAU KECAMATAN DAYUN KABUPATEN SIAK - Rifai, Ahmad; Yulida, Roza; ', Philippus (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Poverty is one of the most important issue in the development of economy of Indonesia. The village empowerment program (Program Pemberdayaan Desa) through Usaha Ekonomi Desa Simpan Pinjam has been established to reduce poverty in the village. The aim of this study is to analyse social performance, economic performance, and to formulate strategy of LKM UED-SP Sejahtera. This research uses outreached analysis to asses social performance, and PEARLS analysis to assess financial performance. The results show that the social performance measured by social objective and mission, dimension activities and internal system, and the output & outcome of the mission has improved significantly. Financial performance that measured through six indicators is ideal while using eleven indicators shows that it is not ideal. The social performance improvement is shown through the improvement of saving volume, development of product innovation, and staff incentives while financial performance imply in asset improvement, risked reserve fund, and saving improvement. Keywords: UED-SP, Microfinance, Social Performance, Economic Performance